Meaning and making: Merchandise practices in the Newcastle DIY scene. (1st March 2018) - Burns, Ruairi; Threadgold, Steven
This article explores the relationships between young punk and indie musicians and the merchandise that they produce. Three interlinking analytic distinctions are made in this article of the young musicians' motivations to make merchandise: building symbolic capital; building economic capital; and serious play. We propose that DIY merchandising entails the construction of an ethical and authentic self through the social gravity of a deeply invested illusio. The research takes place in the DIY music scene of Newcastle, a large regional town on the east coast of Australia. The participants play in punk and indie bands; however, there is a diversity of merchandising practices within the group, highlighting the fluid and complex boundaries of contemporary punk practices. The forms of experimentation, negotiation and strategy encountered illustrate how these meaningful forms of labour are important to struggles about identity and authenticity. Developing and honing merchandise-related skills as a form of 'serious play' has facilitated pathways towards self-employment for several of the participants. For this reason, this article draws attention to the diverse applications for expertise in merchandising, manifesting not only in the music scene but in various fields of social life. These circumstances illustrate interesting sociological developments in youth music scenes regarding music-related practices, employment transitions, labour and the transferring of capitals. The social relationships involved in merchandising are analytically explored using a Bourdieusian framework that considers punk as a social practice.